Prevalence of Mental Disorders in The Community Lamongan-Indonesia: Results of Early Detection with The Community Mental Health Nursing (CMHN) Approach - Aris, Arifal; Yusuf, Ah.; Faridah, Virgianti Nur; Sholihah, Siti; Rokhman, Abdul; Suhariyati, Suhariyati; Sairozi, Ali (International Journal of Psychosocial Rehabilitation, 2020)
Mental disorders are a common problem among people and they have an additional burden on the state and lead to a decrease in human productivity. The purpose of this study was to estimate the prevalence of mental disorders in Lamongan-Indonesia with the community mental health nursing approach. The research method used descriptive design. This research was conducted in the area of the community from 2017 to 2018. It involves researchers and was done in collaboration with 140 (121 women and 19 men) mental health workers for early detection. The respondents in this research were 2385 families. The sampling technique in this study was multistage random sampling. The variable of this study is mental disorders in the families. The evaluation of mental disorders was done using interviews and questionnaires developed by the East Java Province Mental Health Team. Analysis of the data used a univariate analysis with frequency tabulation. Symptoms of mental disorders were detected in 87 families (3.6%), 530 families (22.2%) were at risk of mental disorders, and 1768 families (74.2%) were in good mental health. Among the 87 families who have symptoms of mental disorders, 51 (58, 6%) were treated pharmacologically by reason of insanity. From the early detections, there are still families that show symptoms of mental disorders and the risk of mental disorders. It shows the need for systematic monitoring of the status of mental disorders in the community.